2011
DOI: 10.1590/s1516-89132011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plastic mulch on growth and yield of chilli (Capsicum annuum L.)

Abstract: In this work a field study was conducted to evaluate the effect of coloured plastic mulch on growth and yield of chilli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
61
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 9 publications
43
61
2
1
Order By: Relevance
“…On the other hand, Singh et al reported that mulch could improve leaf photosynthetic capacity beside the role of polyethylene for enhanced root growth, as well as, absorption of each of water and nutrients and thereby, enhanced metabolic activities within plant during the period of growth and reproduction process, which possessed much shoot number per plant and width leaf area with high leaf chlorophyll content as mentioned before that induced more photosynthetic rates. This in turn built high yield of carbohydrates which gave rise to more cell division and enlargement inducing more vegetative vigorous plants ,this reflect to produce more total yield as mentioned by Our results are in agreement with those results obtained with [28]on pepper and [32]on tomato [33][34][35][36][37]. …”
Section: Fruit Characteristicssupporting
confidence: 93%
“…On the other hand, Singh et al reported that mulch could improve leaf photosynthetic capacity beside the role of polyethylene for enhanced root growth, as well as, absorption of each of water and nutrients and thereby, enhanced metabolic activities within plant during the period of growth and reproduction process, which possessed much shoot number per plant and width leaf area with high leaf chlorophyll content as mentioned before that induced more photosynthetic rates. This in turn built high yield of carbohydrates which gave rise to more cell division and enlargement inducing more vegetative vigorous plants ,this reflect to produce more total yield as mentioned by Our results are in agreement with those results obtained with [28]on pepper and [32]on tomato [33][34][35][36][37]. …”
Section: Fruit Characteristicssupporting
confidence: 93%
“…The silver/black and black plastic mulch blocked the weeds, except a few, which emerged through the planting holes. This result is consistent with the findings of Reference [22] and [1]. Similar results were found for weed density.…”
Section: International Journal Of Environmentalsupporting
confidence: 93%
“…Reference [14] reported that tomato grown under irrigation in semi-arid zone of northern Nigeria benefited greatly from mulches. The highest weed dry weight was recorded in transparent plastic mulch and the lowest in black plastic [1]. Black mulch effectively stops weed growth by intercepting nearly all-incoming radiation.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, Veeranna et al, (2001) recorded a yield increase of 9 per cent with the adoption of drip irrigation over furrow method. The increase in yield might be due to better proportion of air-soil-water and suppressed weed growth which was maintained throughout the life period of crop in plastic mulching and drip fertigation @ 120% RDF as reported by Ashrafuzzaman et al, (2011). The increased yield in fertigation treatments might be due to better availability of plant nutrients and irrigation water throughout the crop growth period under drip fertigation system.…”
Section: Resultsmentioning
confidence: 63%